Playful sport design: a lever to enhance engagement and performance (Sport and Exercise Psychology, 2026)
Play represents a central component of the sport experience during developmental years, yet it tends to progressively lose ground as athletes move into competitive and professional contexts, where the focus shifts primarily toward performance. Within this framework, Playful Sport Design (PSD) is conceptualized as a proactive cognitive-behavioral strategy through which athletes autonomously integrate playful and challenging elements into their training experience, with the aim of sustaining engagement and enhancing its functional value for performance. This article introduces Playful Sport Design by outlining its theoretical foundations and synthesizing the main empirical evidence regarding its association with sport engagement and performance. Building on this evidence, the study examines Playful Sport Design in youth amateur and professional soccer contexts, investigating whether the spontaneous use of Designing Fun and Designing Competition strategies is differentially associated with coach-rated performance across competitive levels. The research model was tested on a sample of 159 young soccer players. Results reveal an interaction between PSD and competitive level: in amateur contexts, higher levels of PSD—particularly the Designing Fun component—are associated with more positive coach-rated performance, whereas this association does not emerge in professional contexts. These findings offer theoretical and practical insights for sport research and practice.
Keywords: Playful Sport Design; Sport Engagement; Youth Soccer; Athlete Proactivity; Sport Performance